The Oil Price and Exchange Rate Relationship Revisited: A time-varying VAR parameter approach - Vincent Brémond; Emmanuel Hache; Tovonony Razafindrabe (The European Journal of Comparative Economics, 2016)
The aim of this paper is to study the relationship between the effective exchange rate of the dollar and the oil price dynamics from 1976 to 2013. We explore the links between financial factors (exchange rate, monetary policy, international liquidity) and the oil price volatility. Using a Bayesian time-varying parameter vector auto-regressive estimation we demonstrate that the “historical coincidence” of oil and financial crises can be explained by the specificities of the relationship between these two commodities. The results of this paper are twofold. The US Dollar effective exchange rate elasticity of crude oil prices is not constant across time and remains negative from 1989: a depreciation of the effective exchange rate of the dollar triggers an increase of crude oil prices. This paper also demonstrates the contagion of financial commodities markets development upon the global economy.